Web-Based Public Complaint System Using First In First Out Algorithm in Minahasa Regency: Sistem Pengaduan Masyarakat Berbasis Web dengan Algoritma First In First Out di Kabupaten Minahasa - Moningkey, Efraim Ronald Stefanus; Ropa, Sifra; Kenap, Audy A. (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Efficient and transparent complaint management is a key component of improving public services in local governments. Specific Background: At the Minahasa Regency Investment and One-Stop Integrated Services Office, complaint handling has been performed manually, leading to slow responses, lack of transparency, and administrative inefficiencies. Knowledge Gap: Previous studies have focused on web-based complaint platforms but have not addressed simple and fair queuing mechanisms to manage incoming reports. Aim: This study aims to design and implement a web-based complaint management system that applies the First In First Out algorithm to structure the handling of public complaints. Results: The developed system successfully organized complaints according to arrival order, reduced response time from three–five days to one–two days, improved administrative workflows, and provided real-time monitoring for users and administrators. Novelty: Unlike prior approaches that used priority or round robin scheduling, this study integrates First In First Out to ensure fairness and clarity in processing sequences, proven through real implementation. Implications: The system contributes to digital governance by strengthening transparency, accountability, and efficiency in local public service management. Highlight First In First Out algorithm ensures fair and structured complaint handling. System reduces response time and improves administrative efficiency. Real-time monitoring builds public trust and supports digital governance. KeywordFirst In First Out Algorithm, Web-Based System, Online Complaint System, Public Service, Minahasa Regency